Leiomyosarcoma of the upper respiratory tract: A case report and review of literature - Milić Perović, Marija; Šolajić, Nenad; Rakić, Nebojša; Vučković Hardi, Lidija (Vojnosanitetski pregled, 2021)
Introduction.  Leiomyosarcoma is a malignant smooth muscle tumor that is most often found in the gastrointestinal tract, uterus, and retroperitoneum.  It is uncommon in the upper respiratory tract. Case report. A 53-year-old woman sought treatment for a 3-month history of nasal obstruction and facial pain. An endoscopic examination revealed a polypoid mass involving the right nasal cavity. The patient was operated on. During surgery, a bulky tumor mass was found, which involved the posterior part of the right inferior concha projecting into the lumen of the epipharynx and upper part of the oropharynx. The lesion was completely excised with adequate margins of uninvolved tissue. Histologic slides stained with hematoxylin and eosin showed interlacing fascicles of atypical spindle-shaped cells. Mitotic figures and bizarre giant cells were frequently observed. Immunohistochemical staining revealed that the tumor was positive for smooth muscle actin and h-caldesmon and negative for S-100. Histological and immunohistochemical features were consistent with leiomyosarcoma. The follow-up was regularly performed by nasal endoscopy and computed tomography, and the disease-free period has been 53 months so far. Conclusion. To the best of our knowledge, this is the longest disease-free period in a patient with leiomyosarcoma of the upper respiratory tract since 1996. This tumor has obscure clinical behavior and prognosis, thus we believe it is necessary to have more published data to determine the best combination of existing therapies, as well as potential new therapies, and enable a longer survival period.
Keywords: diagnosis, differential; leiomyosarcoma; histological techniques; otorhinolaryngologic surgical procedures; pharyngeal neoplasms; respiratory system; survival